« Et voilà qu’arrive l’aventure ! » - Léonore Le Caisne (Criminocorpus)
Lannemezan prison, autumn 1994, Daniel Koehl (age 38), a.k.a. Coin-Coin, convicted in 1978 to life imprisonment at the age of 21 for murder, recounts his prison career to Pierre-Marie Andreotti (aged 47), also sentenced to life imprisonment for murder. The first one has been in prison for nearly seventeen years, the second one for fourteen years. Both are "particularly reported inmates" (DPS). In this excerpt, Daniel Koehl recalls the mutiny at the Saint-Maur prison in 1987, of which he was one of the main leaders. The ultra-secure prison, built twelve years before, was completely destroyed during the mutiny.